Effects of gamma irradiation on the shelf-life of frozen tiger shrimp, Penaeus monodon (Fabricius, 1798) - Mustafa, MG; Hossain, MA; Alam, MJ; Khan, MMR; Nilla, SS; Alam, MZ (International Journal of Natural Sciences, 2016)
The effects of three levels of irradiation (3, 6 and 9 KGy) during storage period (0, 15, 30, 45, 60, 75 and 90 days) were evaluated in frozen tiger shrimp, Penaeus monodon. Biochemical composition was analyzed before and after treatment. Quality of tiger shrimp was assessed through organoleptic, chemical (Total Volatile Nitrogen, TVN and Trimethylamine, TMA) and microbiological (Total Bacterial Count (TBC); Total Mold Counts (TMC); Total Yeast Count, (TYC); Total Coliform Count, (TCC) and Salmonella count) evaluation at an interval of 15 days during the storage period. High doses of radiation affected on the texture of fish. While, the maximum shelf life was observed for 9 KGy irradiated sample. All the samples were acceptable during 90 days of storage period because the upper limit of all spoilage indicators did not exceed the recommended values. International Journal of Natural Sciences (2014), 4(1) 10-15